Notice of a Highland Powder Horn, having on it the Monogram of Sir George Mackenzie; with some Remarks on Highland Costume. (The Horn, with others of various kinds, was exhibited.) (Proceedings of the Society of Antiquaries of Scotland, 1873)
[The journal notes that this paper will be published in the Archaeologia Scotica.]